Molybdoenzymes and molybdenum cofactor in plants - Mendel, Ralf R (Journal of experimental botany, 2002)
The transition element molybdenum (Mo) is essential for (nearly) all organisms and occurs in more than 40 enzymes catalysing diverse redox reactions, however, only four of them have been found in plants. (1) Nitrate reductase catalyses the key step in inorganic nitrogen assimilation, (2) aldehyde oxidase(s) have been shown to catalyse the last step in the biosynthesis of the phytohormone abscisic acid, (3) xanthine dehydrogenase is involved in purine catabolism and stress reactions, and (4) sulphite oxidase is probably involved in detoxifying excess sulphite. Among Mo-enzymes, the alignment of amino acid sequences permits domains that are well conserved to be defined. With the exception of bacterial nitrogenase, Mo-enzymes share a similar pterin compound at their catalytic sites, the molybdenum cofactor. Mo itself seems to be biologically inactive unless it is complexed by the cofactor. This molybdenum cofactor combines with diverse apoproteins where it is responsible for the correct anchoring and positioning of the Mo-centre within the holo-enzyme so that the Mo-centre can interact with other components of the enzyme's electron transport chain. A model for the three-step biosynthesis of Moco involving the complex interaction of six proteins will be described. A putative Moco-storage protein distributing Moco to the apoproteins of Mo-enzymes will be discussed. After insertion, xanthine dehydrogenase and aldehyde oxidase, but not nitrate reductase and sulphite oxidase, require the addition of a terminal sulphur ligand to their Mo-site, which is catalysed by the sulphur transferase ABA3